An Enterprise Architecture Blueprint for HL7-Based RIS–PACS Integration Using TOGAF ADM: A Mobile Diagnostic Access Framework - Purnama, Wandi; Indrajit, Richardus Eko; Firizqi , Januponsa Dio (Sinkron : jurnal dan penelitian teknik informatika, 2026)
The shift to digital radiology is frequently hindered by data fragmentation and restricted mobility for healthcare professionals. This research addresses these deficiencies by developing an Enterprise Architecture (EA) blueprint for hospital radiology departments using the TOGAF ADM framework. The design emphasizes HL7 standards for administrative data transfer and DICOM protocols for imaging, featuring a web-based Mobile Viewer using the WADO protocol for remote high-resolution access. Architectural validation via gap analysis demonstrates that the proposed integration can theoretically eliminate manual data entry between HIS and RIS-PACS through an HL7 broker mechanism, potentially shortening clinical report turnaround times. However, this study is limited to architectural validation and does not include live clinical deployment. The proposed architecture offers a scalable roadmap for "film-less" environments, though further longitudinal studies are required to assess long-term clinical user satisfaction.